2022
DOI: 10.1016/j.waojou.2021.100620
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hereditary angioedema in a Chinese cohort with decreased complement 4 levels

Abstract: Objective: Hereditary angioedema (HAE) is a rare, life-threatening autosomal dominant disorder.We aimed to investigate the prevalence of HAE in a Chinese population with a decreased Complement 4 (C4) level. Methods:All the patients present in Tongji Hospital with C4 below lower normal range were included from January 2019 to June 2020. The individual data were extracted from the database and categorized by diagnosis. Patients suspected of HAE were further evaluated by C1 inhibitor level and function test to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The prevalence of HAE in Black patients (1.64 cases per 100,000) was almost similar to that of White patients (1.47 cases per 100,000), whereas it was lower among Hispanic patients (0.80 cases per 100,000) [ 47 ]. Furthermore, according to a study conducted in Tongji Hospital in China, the prevalence of HAE was reported to be 2.43 cases per 10,000 in patients with decreased complement 4 level [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of HAE in Black patients (1.64 cases per 100,000) was almost similar to that of White patients (1.47 cases per 100,000), whereas it was lower among Hispanic patients (0.80 cases per 100,000) [ 47 ]. Furthermore, according to a study conducted in Tongji Hospital in China, the prevalence of HAE was reported to be 2.43 cases per 10,000 in patients with decreased complement 4 level [ 19 ].…”
Section: Resultsmentioning
confidence: 99%